Pendampingan UMKM melalui Penyediaan Lapak dalam Meningkatkan Perekonomian Masyarakat - Asfahani Asfahani; Asysta Amalia Pasaribu; A Idun Suwarna (Edujavare Publishing, 2023)
In many countries, MSMEs are often faced with various obstacles such as limited capital, limited access to markets, and lack of managerial skills. Providing stalls for MSMEs can be an effective strategy in helping them expand their market reach and increase product visibility. The aim of this service is to assist MSMEs through providing stalls to improve the community's economy. The method used in this service research is the ABCD method. From the results of this research discussion, it can be concluded that mentoring MSMEs through the provision of stalls has a positive impact in improving the community's economy. Lapak not only provides opportunities for MSMEs to expand market reach and increase sales, but also creates closer relationships between business actors and consumers, which can contribute to the development of local communities.